Auxiliary proteins that facilitate formation of collagen‐rich deposits in the posterior knee capsule in a rabbit‐based joint contracture model. Issue 3 (18th August 2015) - Steplewski, Andrzej; Fertala, Jolanta; Beredjiklian, Pedro K.; Abboud, Joseph A.; Wang, Mark L. Y.; Namdari, Surena; Barlow, Jonathan; Rivlin, Michael; Arnold, William V.; Kostas, James; Hou, Cheryl; Fertala, Andrzej
ABSTRACT: Post‐traumatic joint contracture is a debilitating consequence of trauma or surgical procedures. It is associated with fibrosis that develops regardless of the nature of initial trauma and results from complex biological processes associated with inflammation and cell activation. These processes accelerate production of structural elements of the extracellular matrix, particularly collagen fibrils. Although the increased production of collagenous proteins has been demonstrated in tissues of contracted joints, researchers have not yet determined the complex protein machinery needed for the biosynthesis of collagen molecules and for their assembly into fibrils. Consequently, the purpose of our study was to investigate key enzymes and protein chaperones needed to produce collagen‐rich deposits. Using a rabbit model of joint contracture, our biochemical and histological assays indicated changes in the expression patterns of heat shock protein 47 and the α‐subunit of prolyl 4‐hydroxylase, key proteins in processing nascent collagen chains. Moreover, our study shows that the abnormal organization of collagen fibrils in the posterior capsules of injured knees, rather than excessive formation of fibril‐stabilizing cross‐links, may be a key reason for observed changes in the mechanical characteristics of injured joints. This result sheds new light on pathomechanisms of joint contraction, and identifies potentially attractive anti‐fibrotic targets. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:489–501, 2016.